2011
DOI: 10.1007/s10120-011-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Depth-predicting score for differentiated early gastric cancer

Abstract: Background Intramucosal and minute submucosal (M-SM1; \500 lm in depth) differentiated gastric cancers, which have a negligible risk of lymph node metastasis, are the targets for endoscopic resection. However, there have been few reports about the endoscopic distinction between these cancers and cancers with deeper submucosal invasion (SM2; C500 lm in depth). The aim of this retrospective study was to analyze the differences in the endoscopic features between M-SM1 and SM2 cancers, and to develop a simple scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 14 publications
4
77
0
Order By: Relevance
“…The first is that previously reported diagnostic markers of invasion depth, such as tumor diameter, macroscopic type, and coloration [4,5,6,7], are markers based on statistical correlations that are independent of histopathological features. In contrast, the non-extension sign is a marker with a direct causal link to the histopathological features of SM2 invasion, which suggests high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is that previously reported diagnostic markers of invasion depth, such as tumor diameter, macroscopic type, and coloration [4,5,6,7], are markers based on statistical correlations that are independent of histopathological features. In contrast, the non-extension sign is a marker with a direct causal link to the histopathological features of SM2 invasion, which suggests high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, determination of the depth of invasion has been based on the experience of the endoscopist, using a number of different indices of depth of invasion as derived from statistical analyses of the morphological characteristics of SM2 cancers [4][5][6][7]. Since the morphology of EGCs is readily altered by the degree by which the gastric wall is extended by insufflated air, this diagnostic marker lacks both objectivity and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in endoscopy [8], endoscopic ultrasonography [9], and multidetector computed tomography (MDCT) [10], several techniques have been established that provide satisfactory diagnostic data regarding the appropriate depth of invasion. A previous study regarding LN evaluation reported the improved diagnostic accuracy of MDCT [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sekiguchi et al [7] identified submucosal (SM) invasion as an independent risk factor for LV invasion in endoscopically resected gastric cancer. Despite extensive efforts [8,9], correct diagnosis of the invasion depth, prior to ESD remains a challenge. When SM/LV invasion is detected following careful pathological examination of endoscopically resected specimens, further surgical treatment, such as gastrectomy with LN dissection, is needed.…”
Section: Introductionmentioning
confidence: 99%